2013
DOI: 10.1103/physrevb.87.235311
|View full text |Cite
|
Sign up to set email alerts
|

Edge channel transport in the InAs/GaSb topological insulating phase

Abstract: Transport in InAs/GaSb heterostructures with different InAs layer thicknesses is studied using a six-terminal Hall bar geometry with a 2-µm edge channel length. For a sample with a 12-nm-thick InAs layer, non-local resistance measurements with various current/voltage contact configurations reveal that the transport is dominated by edge channels with negligible bulk contribution. Systematic non-local measurements allow us to extract the resistance of individual edge channels, revealing sharp resistance fluctuat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
161
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(179 citation statements)
references
References 26 publications
11
161
3
Order By: Relevance
“…Apparently, this mode cannot be readily assigned as any of the predicted SL modes. [7][8][9][10] It should be interpreted as a transverse counterpart of the GaSb QC-LO with A 1 symmetry split due to the phonon-polariton effect. And it is also the only mode showing observable anisotropy between and to be discussed later.…”
Section: (110) and (-110) Cleaved Edge Back-scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, this mode cannot be readily assigned as any of the predicted SL modes. [7][8][9][10] It should be interpreted as a transverse counterpart of the GaSb QC-LO with A 1 symmetry split due to the phonon-polariton effect. And it is also the only mode showing observable anisotropy between and to be discussed later.…”
Section: (110) and (-110) Cleaved Edge Back-scatteringmentioning
confidence: 99%
“…[1] These differences make the electronic structure and vibration spectrum of InAs/GaSb heterostructure more complex and intriguing, and also less well understood. Besides using InAs/GaSb type II superlattices (T2SLs) for IR detection, [2,3] InAs/GaSb heterostructures have lately been explored for fundamental interests, such as exciton condensation, [4,5] quantum spin Hall effect or topologic insulator, [6][7][8][9][10] and graphene-like Dirac fermion. [11] Raman spectroscopy is widely used for studying lattice vibrations and probing electronphonon coupling in semiconductor SLs.…”
mentioning
confidence: 99%
“…They found that beyond a critical thickness of the HgTe QW, the TI state would appear as confirmed experimentally. [6][7][8][9] Furthermore, interesting experimental progress on 2D TI properties has also been achieved in InAs/GaSb QWs [26][27][28] as proposed theoretically. 29 Hyperfine (HF) interactions between the electron and nuclear spins can play an important role in nanostructureseven though it is often weak.…”
Section: Introductionmentioning
confidence: 99%
“…Using the matrix elements in Eqs. (27) and (29), we now finally arrive at the HF interactions relevant for the P -like states in the basis (7) as…”
Section: The Hf Interactions For P-like Statesmentioning
confidence: 99%
“…If the Fermi energy is tuned to be inside this gap, transport should be dominated by helical edge channels. First experimental signs of such states in InAs/GaSb CQW samples smaller than the phase coherent length were recently reported [5][6][7] . In all studies, the principal issue is the residual conductivity from the bulk which is attributed to sample disorder and obscures the visibility of the dissipationless edge channel transport.…”
mentioning
confidence: 93%